2015
DOI: 10.1063/1.4936425
|View full text |Cite
|
Sign up to set email alerts
|

Rotational dynamics of a diatomic molecular ion in a Paul trap

Abstract: We present models for a heteronuclear diatomic molecular ion in a linear Paul trap in a rigidrotor approximation, one purely classical and the other where the center-of-mass motion is treated classically, while rotational motion is quantized. We study the rotational dynamics and their influence on the motion of the center-of-mass, in the presence of the coupling between the permanent dipole moment of the ion and the trapping electric field. We show that the presence of the permanent dipole moment affects the t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Such a conclusion is also supported by other theoretical derivations [20][21][22] and numerical simulations of the wave-packet dynamics [23]. While these studies pertain to atomic ions, non-polar molecules have the same centre-of-mass trajectories as atomic ions, and we have also recently shown that the interaction between the trapping field and a dipole moment doesn't lead to a noticeable modification of the stability criterion [24].…”
Section: Introductionsupporting
confidence: 78%
“…Such a conclusion is also supported by other theoretical derivations [20][21][22] and numerical simulations of the wave-packet dynamics [23]. While these studies pertain to atomic ions, non-polar molecules have the same centre-of-mass trajectories as atomic ions, and we have also recently shown that the interaction between the trapping field and a dipole moment doesn't lead to a noticeable modification of the stability criterion [24].…”
Section: Introductionsupporting
confidence: 78%
“…We derived the effective trapping potential for aspherical objects with non-vanishing permanent electric multipole moments in quadrupole ion traps, and numerically demonstrated cooling in a realistic setup. The derived relations will be relevant for quantum experiments with charged molecules and nanoparticles [27,33,[38][39][40]68].…”
Section: Discussionmentioning
confidence: 99%
“…The endcaps are held at a voltage of U ec with respect to ground. This trap geometry was used for instance in the experiments reported in [38,39,68].…”
Section: B Linear Paul Trapsmentioning
confidence: 99%
See 1 more Smart Citation
“…All thermodynamical or statistical properties can be obtained from the partition function since it contains all the information about the given system [1]. A basic example is provided by the ideal quantum gas of di-atomic molecules, whose properties have been extensively studied in atomic, and molecular physics [2,3,4,5]. Di-atomic molecules are described be it as rigid or elastic dumbbells with the dumbbells tracing trajectories placed on a two-dimensional space of constant curvature, the sphere immersed into a flat three-dimensional space.…”
Section: Introductionmentioning
confidence: 99%